2012
DOI: 10.3892/ol.2012.943
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of patients with synchronous primary endometrial and ovarian cancers: A review of 43 cases

Abstract: Abstract. Synchronous primary endometrial and ovarian cancers are uncommon. The purpose of this study was to evaluate the clinicopathological characteristics, treatment and prognosis of synchronous primary endometrial and ovarian cancers. The clinicopathological characteristics of 43 patients with synchronous primary endometrial and ovarian cancers in the Obstetrics and Gynecology Hospital of Fudan University between 1999 and 2009 were retrospectively reviewed. Our results revealed that the median age at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 9 publications
11
44
0
Order By: Relevance
“…They reported 7 cases of ovarian mucinous carcinomas with endometrioid endometrial carcinomas in their study .Sylwia et al reported 10 cases of which 1 was ovarian mucinous carcinoma with endometrioid endometrial carcinoma [9] . Age of presentation in our case was 51 years which is correlating with previous studies [7].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…They reported 7 cases of ovarian mucinous carcinomas with endometrioid endometrial carcinomas in their study .Sylwia et al reported 10 cases of which 1 was ovarian mucinous carcinoma with endometrioid endometrial carcinoma [9] . Age of presentation in our case was 51 years which is correlating with previous studies [7].…”
Section: Discussionsupporting
confidence: 80%
“…Previous reports do suggest that majority of synchronous tumours present at stage I [4,7] . The treatment of synchronous endometrial and ovarian cancer depends on the pathological characteristics of each tumour [4,11] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations